A theoretical and experimental investigation of jet-pump refrigeration system - Ablwaifa, Ali E. (2006)
This thesis describes a theoretical and experimental investigation of the jet-pump refrigerator, and the application of Computational Fluid Dynamics (CFD) to improve the performance of the jet-pump, which lies at its heart.